What is qualitative longitudinal research? - Neale, Bren (What is? research methods series., 2019)
"This volume offers a definitive introduction to a major new research method in the social sciences. Qualitative Longitudinal Research is defined broadly as qualitative enquiry that is conducted through, or in relation to time. The approach is not new; it forms part of a rich ethnographic tradition spanning social anthropology, oral history, community studies and theatre research. However, in recent years a new body of scholarship has emerged seeking to delineate the method and promote it as a distinctive way of knowing and understanding the social world, and a growing number of studies, ranging from the lived experience of welfare reform, to the dynamics of energy use have been conducted using QL analysis. This practical volume will be a first port of call for students and researchers wishing to use QL research in their own projects. The chapters follow a logical development from conceptual and methodological foundations, to research practice and ethics, to the analysis, management and presentation of datasets. The book concludes by looking at the practical application and utility of this method in varied substantive contexts. Each chapter offers practical examples drawn from the research field to illustrate key themes and the rich possibilities for new applications, addressing the challenges of the methods and how critiques might be addressed. Pedagogical materials include boxes of frequently asked questions and recommended reading and the book includes a glossary of key terms."--